Malawi - Country Economic Memorandum : Seizing Opportunities for Growth through Regional Integration and Trade - Summary of Main Finding and Recommendations - World Bank (World Bank, 2012)
Malawi needs to focus on exports to maintain and broaden its current inspiring levels of economic growth. The focus of future policy should therefore be on reforms that improve competitiveness in global and regional markets. This does not require a fundamental shift in direction, but instead a rebalancing of policy and expenditures to support an outward-oriented development framework. Until the recent global financial crisis, domestic and regional trends were promising for Malawi: rapid economic growth, strong donor support, increases in foreign direct investment, real potential to upgrade regional infrastructure, and the gradual dismantling of barriers within the region through the Common Market for Eastern and Southern Africa (COMESA) and Southern Africa Development Community (SADC) free trade areas. Despite recent global developments, this report makes the case that, for a small landlocked economy like Malawi, integration into a dynamic and more open Southern Africa region will remain a key to building prosperity and improving livelihoods.